1994
DOI: 10.1093/infdis/169.3.547
|View full text |Cite
|
Sign up to set email alerts
|

Outbreaks of Salmonella enteritidis Infections in the United States, 1985-1991

Abstract: The spread of Salmonella enteritidis infections in the United States was tracked to identify potential risk factors and preventive measures. Isolation rates and information regarding outbreaks of S. enteritidis from 1985 through 1991 were determined by reports to the national Salmonella surveillance system and through the foodborne disease outbreak surveillance system. From 1985 through 1991, 380 outbreaks were reported involving 13,056 ill persons and 50 deaths. The proportion of Northeast outbreaks fell from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
101
1
3

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(108 citation statements)
references
References 17 publications
1
101
1
3
Order By: Relevance
“…Epidemiological investigations have shown that poultry, poultry products, pork and raw milk are the most common sources of sporadic outbreaks of human salmonellosis 19,20,32 .…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological investigations have shown that poultry, poultry products, pork and raw milk are the most common sources of sporadic outbreaks of human salmonellosis 19,20,32 .…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have reported that salmonellosis outbreaks were associated with poultry meat or eggs [9,18,29]. Vertical transfer of infections from breeding hens to progeny has been an important aspect of the epidemiology of Salmonella species infections within the poultry industry [1,7,8,12,30].…”
mentioning
confidence: 99%
“…Rates increased from Ͻ1 case per 100,000 inhabitants before 1994 to 3.5 per 100,000 in that year, with a further increase to 5.4 cases per 100,000 in 1998 (8,9). These infections have been related to the consumption of inadequately cooked S. enterica serotype Enteritidis-contaminated poultry items (2,11,12,(20)(21)(22). During surveillance studies in Chile, S. enterica serotype Enteritidis isolates have been found in ϳ1 of every 1,000 egg samples and 7% of poultry meat offered at retail markets in the metropolitan area (1).…”
mentioning
confidence: 99%